Limited access to land rights for the powerless in Potchefstroom - N.S. Jansen van Rensburg (Koers : Bulletin for Christian Scholarship, 1995)
The concept of structural violence is useful in the analysis of the land issue in urban areas in South Africa, more specifically in this case, the town of Potchefstroom from 1901 to 1952. By institutionalising racism, a situation of inequality of power and opportunities has been brought about. This can best be understood within the rigidly stratified system of apartheid: it imposed an alternative and restricted structure of land use on the specific subordinate category in the area of study. By creating this alternative system, those in power excluded the powerless from the "central" system. The concept of an alternative system can be understood in terms of the theory of structural violence, to explain the difference between the real and the potential attainment of human somatic and psychical abilities. Thus, structural violence is built into the very structures of a society and is concretized in unequal power and, consequently, unequal opportunities in life. Clearly, group and institutional discrimination in this area can be viewed as a form of structural violence because of the dire consequences, the indirect methods and the impersonal nature of these actions.